DIGITAL TRANSFORMATION AND THE RISK OF EXCLUSION: IMPLEMENTATION OF THE MOBILE JKN ONLINE QUEUEING SYSTEM IN OUTPATIENT SERVICES - Michael Sabatino Sitompul; Ermi Girsang; Sri Lestari Ramadhani Nasution (Pusat Studi Gender dan Anak, 2026)
Digital transformation has become a priority for health systems in the Industry 4.0 era, yet its benefits are not distributed evenly across patient groups. Dr. Pirngadi General Hospital, Medan, has implemented an online queueing system through the Mobile JKN application; however, its utilisation remained low, reaching only 9.16% of outpatients (4,709 of 51,419) during January–September 2025.To analyse the implementation of the Mobile JKN online queueing programme in outpatient services using Rogers’ Diffusion of Innovations framework (relative advantage, compatibility, complexity, trialability, and observability), with particular attention to factors that may exclude vulnerable users. A qualitative case study was conducted from February to April 2026. Twelve informants (eight outpatient Mobile JKN users, one outpatient nurse, one administrative coordinator, one IT staff member, and one BPJS Kesehatan person-in-charge) were selected purposively until data saturation. Data were gathered through in-depth interviews, direct observation, and document review, and analysed using thematic analysis. Trustworthiness was established through source and technique triangulation. In terms of relative advantage, the system reduced physical queues and paper logistics and shortened administrative processing through automatic population of the hospital information system (SIMRS). Compatibility was supported by integration via Bridging System v2.0, but a misfit emerged for elderly and non-smartphone users. Complexity was the dominant barrier, centred on account activation requiring phone credit and an internet connection, and on low digital literacy among older patients. Trialability and observability were adequate, monitored through the quality rate (QR) indicator reported every 3–7 days; the QR initially fell below the >85% target but improved with continuous evaluation. The programme delivers clear efficiency gains, but its low uptake reflects a digital divide driven by patient demographics and technological constraints rather than by system design. Targeted digital-literacy support and assisted-registration services for technology-vulnerable groups are required to make the innovation genuinely inclusive.